Perbandingan Penggunaan APACHE IV, SAPS 3 dan SOFA untuk Memprediksi Mortalitas pada Pasien Kritis - Hesti Prawita W; Suharyo Hadisaputro; Supriyadi Supriyadi (Poltekkes Kemenkes Semarang, 2015)
The objective of this study is to compare the validation scoring system of APACHE IV, SAPS 3 and SOFA to predict mortality in critically ill patients. The type and design of the study is an observational analytic with cross-sectional design with retrospective sampling conducted using the secondary data. The otal sample is 106 respondents who were treated in the ICU of A. Wahab Sjahranie Hospital Samarinda between January - October 2013. The results of bivariant analysis showed that there was a statistically significant relationship between the three scoring systems (APACHE IV, SAPS 3 and SOFA) with the outcomes of respondents with a value of p less than 0.05 (p = 0.004 APACHE IV; SAPS 3 p = 0.004 and SOFA p = 0.022). APACHE IV AUROC = 0.757; AUROC SAPS 3 = 0.717; AUROC SOFA = 0.69. Calibration of APACHE IV with a value of p = 0.20; SAPS 3 p = 0.086 and p = 0.60 SOFA.Conclusion: APACHE IV has better discrimination and calibration compared with the SAPS 3 and SOFA. Suggestion: APACHE IV should be using to predict mortality in critically ill patients.